Old English adjectival affixation: Structure and function - Vea Escarza, Raquel (Adam Mickiewicz University, 2013)
The aim of this article is to carry out a structural-functional analysis of the formation of Old English adjectives by means of affixation. By analysing the rules and operations that produce the 3,356 adjectives which the lexical database of Old English Nerthus (www.nerthusproject.com) turns out as affixal derivatives, a total of fourteen derivational functions have been identified. Additionally, the analysis yields conclusions concerning the relationship between affixes and derivational functions, the patterns of recategorization present in adjective formation and recursive word-formation.
Keywords: structural-functional linguistics; Process and Paradigm Morphology; Old English; word-formation; adjective; recursivity